RANCANG BANGUN SISTEM INFORMASI PREVENTIVE MAINTENANCE BERBASIS MOBILE - Sahrul Muharom, Alif Alpian (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2024)
The development of information technology has triggered transformations in various aspects of human life, including industries. In the industrial context, technology plays a key role in transforming maintenance practices from reactive to preventive. Although preventive maintenance (PM) offers significant benefits, its manual implementation often faces challenges such as monitoring difficulties, record-keeping, and the risk of human errors. In response to these challenges, technology-based solutions, such as Mobile App-Based Preventive Maintenance, have emerged as effective alternatives with the potential to improve efficiency, reduce operational costs, and avoid human errors. This research aims to enhance the responsiveness and affordability of maintenance, optimize the preventive maintenance process through mobile applications, and design and develop a Mobile-Based Preventive Maintenance Information System. The research was conducted at PT Krakatau Tirta Industri, focusing on the Information Systems and Performance Management division. The theoretical foundation includes concepts of information systems, preventive maintenance, and technologies used in mobile application development, such as Android, Kotlin, Android Jetpack, Jetpack Compose, Firebase, and Figma. The Waterfall method is used as the application development approach. The results of the research indicate that the implementation of this system significantly contributes to the effectiveness and efficiency of the company. The system helps effectively design and build preventive maintenance information systems, assists the maintenance department in performing their tasks better, facilitates administration in managing preventive maintenance data, and provides easy access for the maintenance department to monitor the condition of machines that require repair.